2000
DOI: 10.1093/emboj/19.11.2701
|View full text |Cite
|
Sign up to set email alerts
|

Origins of minigene-dependent growth inhibition in bacterial cells

Abstract: The expression of very short open reading frames in Escherichia coli can lead to the inhibition of translation and an arrest in cell growth. Inhibition occurs because peptidyl-tRNA hydrolase fails to recycle suf®-ciently rapidly peptidyl-tRNA released from ribosomes at the stop signal in competition with normal termination, causing starvation for essential species of tRNA. Previous studies have shown that the last sense codon, the strength of the Shine±Dalgarno sequence and the nature and context of the stop c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 32 publications
2
65
0
Order By: Relevance
“…Overexpression of the IF3 encoding gene, infC, is also predicted to be deleterious to the cell. It is known that ribosome recycling factor (RRF), and elongation factor G (EF-G) cooperate to release small peptidyl tRNAs from ribosomes stalled early in the translation of an open reading frame-this is particularly frequent during the first seven codons translated (Karimi et al 1998;Heurgue-Hamard et al 2000; for review, see Buchan and Stansfield 2007). This may help rapid abandonment of translation under conditions where aminoacyl tRNAs are in limiting supply, namely, as an amino acid starvation early warning system.…”
Section: Why Control By Negative Feedback: Translational Fidelity As mentioning
confidence: 99%
“…Overexpression of the IF3 encoding gene, infC, is also predicted to be deleterious to the cell. It is known that ribosome recycling factor (RRF), and elongation factor G (EF-G) cooperate to release small peptidyl tRNAs from ribosomes stalled early in the translation of an open reading frame-this is particularly frequent during the first seven codons translated (Karimi et al 1998;Heurgue-Hamard et al 2000; for review, see Buchan and Stansfield 2007). This may help rapid abandonment of translation under conditions where aminoacyl tRNAs are in limiting supply, namely, as an amino acid starvation early warning system.…”
Section: Why Control By Negative Feedback: Translational Fidelity As mentioning
confidence: 99%
“…1A). By maintaining the same transcriptional promoter, SD region, initiation and termination codons, and the shortest possible "ORF," we attempted to minimize the number of variables affecting minigene expression and focus on the effect of the different sense codons on toxicity (9,13 Fig. 1B, showed a wide variation in the degree of toxicity to the two mutant strains arising from minigene expression and depending on the nature of the second codon: 27 were toxic to both pth(Ts) and pth(rap), 18 were lethal to pth(rap), and 16 had no deleterious effects on either mutant.…”
Section: Minigenes Harboring Codons From the Same Genetic Codementioning
confidence: 99%
“…Interestingly, a high frequency of AAA/G codons, associated to high drop-off rates in minigenes, has been found at the last sense position of the E. coli ORFs where they also promote drop-off (13). This non-random codon distribution at the ends of ORFs has been considered as an important factor in the modulation of translation termination (39).…”
Section: Minigenes Harboring Codons From the Same Genetic Codementioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that minigene overexpression in E. coli can inhibit both translation and cell growth (14,20). Inhibition occurs because cells fail to cleave the peptidyl-tRNA released from ribosomes efficiently, resulting in depletion of essential tRNA species (14,20).…”
mentioning
confidence: 99%